2010
DOI: 10.1182/blood-2010-03-272278
|View full text |Cite
|
Sign up to set email alerts
|

Genomic alterations reveal potential for higher grade transformation in follicular lymphoma and confirm parallel evolution of tumor cell clones

Abstract: Our aim was to examine the genetics of clonal evolution in follicular lymphoma (FL) and to identify genetic alterations associated with disease progression. A total of 100 biopsies from 44 patients diagnosed with t(14;18)-positive FL were examined by array comparative genomic hybridization. In 20 patients the patterns of somatic hypermutations (SHMs) in the variable region of heavy chain gene were additionally analyzed. Gain of chromosome X in male samples was a marker for poor outcome (P < .01). Gains involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 52 publications
2
30
0
2
Order By: Relevance
“…Gain of X is associated with inferior outcome in FL. [1][2][3][4] Analysis of 131 FL-samples in the LLMPP data set 10,17 confirmed these results (supplemental Figures 2-5). Using Ingenuity Systems Pathway Analysis, the molecular network most enriched for cis-genes was identified ( Figure 1C).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Gain of X is associated with inferior outcome in FL. [1][2][3][4] Analysis of 131 FL-samples in the LLMPP data set 10,17 confirmed these results (supplemental Figures 2-5). Using Ingenuity Systems Pathway Analysis, the molecular network most enriched for cis-genes was identified ( Figure 1C).…”
Section: Resultssupporting
confidence: 55%
“…[1][2][3][4] Most alterations span large genomic regions involving hundreds of genes, thus offering limited cues for identification of genes driving the development of FL. Elevated expression of c-MYC and other genes promoting proliferation, inactivation of TP53 and CDKN2A, dysregulation of p38-mitogen-activated protein kinase (MAPK), and mutations of BCL6 have been implicated in subsets of cases with transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Largely as a result of karyotyping and, more recently, the application of single nucleotide polymorphism (SNP) array profiling and array CGH to FL genome analysis, a relatively complete view of aCNA/LOH and cnLOH in FL has emerged. [12][13][14][15][16][17][18][19][20][21][22][23] The subsequent application of this knowledge to pathogenetic gene discovery has resulted in the identification of novel genes important to the biology of FL. 12,15,24 However, compared with other hematologic malignancies, like diffuse large B-cell lymphoma (DLBCL), chronic lymphocytic leukemia, acute lymphoblastic anemia, or multiple myeloma, the current understanding of the incidence of recurrent gene mutations and the interplay of gene mutations and aCNA/ LOH and cnLOH in FL is in its early stages and largely incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear as to whether immunoglobulin somatic hypermutation occurs in synchronicity with other somatic mutations, and thus whether other somatic events follow identical evolutionary patterns [7 & ]. Indeed, analysis of paired follicular lymphoma and tFL biopsies showed that genomic gains and losses frequently do not follow the same patterns of evolution observed at the level of immunoglobulin somatic hypermutation, and are frequently not conserved between tumors [30,31]. In addition, there have been no gains or losses found to be recurrently conserved between serial biopsies, indicating that DNA copy number alterations are likely not early events during genetic evolution.…”
Section: Divergent Evolutionmentioning
confidence: 91%